The Influence Factors of Tourist Visiting Mumbul Garden Agrotourism PT. Perkebunan Nusantara XII - Hamka Jamal (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research was conducted at Agrotourism Mumbul Garden, PT Perkebunan Nusantara XII. The variables used in this study are service factors (X1), facilities and infrastructure factors (X2), attraction factors (X 3), accessibility factors (X4), and tourist visit decision (Y). This study aims to analyze the influence of the independent variables both simultaneously and partially, as well as to determine the most dominant variable affecting tourists' visit decisions. The analytical techniques used in this research include multiple linear regression analysis, coefficient determination, F-test, and t-test, processed using SPSS version 16.0. The results of this study indicate that: (1) service factors, facilities and infrastructure factors, attraction factors, and accessibility factors have a significant influence on tourists' visit decisions; (2) accessibility factors partially have a significant influence on tourists' visit decisions; and (3) accessibility factors are the most dominant variable influencing tourists' visit decisions.